Widely Used Disciplinary Options for Aggressive Kids: Are the Current Approaches Effective? - Blankenship, Tracy; Bender, William N. (Journal of the American Academy of Special Education Professionals, 2007)
The question of what to do with aggressive students has plagued schools since mandatory attendance laws were passed. At the present time, many practitioners are using tactics for aggressive students that may not effectively remediate the problem, and research and practice do not seem to be in harmony regarding disciplinary options for aggressive students. While the most widely used options continue to be in-school suspension and out-of-school suspension, the research does not seem to support the efficacy of such measures. However, there are many promising practices within the research that deserve more consideration, and some of these have a stronger research support than suspension.